Компетентність і компетенція–ключові поняття компетентнісного підходу в сучасній освіті - Сукаленко, Тетяна Миколаївна; Позднякова, Ольга Олегівна («Аксіома», 2018)
У статті проаналізовано поняття «компетенція», «компетентність», «компетентнісний підхід». Обґрунтовано актуальність компетентнісного підходу, застосування якого обумовлено соціально-економічними потребами сучасного суспільства. Висвітлено використання термінів «компетенція», «компетентність» у сучасній освіті та згруповано основні підходи до їхнього розуміння. Визначення пріоритетності компетентнісного підходу в освіті спрямовано на перехід до нових галузевих стандартів, що створює передумови для реалізації ключових компетентностей у майбутній професійній діяльності майбутнього фахівця відповідно до потреб суспільства та вимог ринку праці.

The paper deals with the analysis of the concept of «competence», «awareness», «competence approach». The relevance of the competence approach, the application of which is conditioned by socio-economic needs of modern society, is substantiated. The use of the terms «competence», «awareness» in modern education is highlighted and the main approaches to their understanding are grouped. The significant features of competence are defined: the ability to make decisions; personal qualities to ensure the desired result in the workplace; a set of individual abilities, that are necessary for the performing of the professional duties; possession of a person with the appropriate competence and attitude to the subject of the activity; the inherent quality of the individual, manifested in the ability and readiness for the acting. The research paper focuses on the lack of a unified interpretation and existence of different views on the essence of the concepts of «competence», «awareness» due to the context; the importance of taking into account the relationship between the growth of awareness and the system of values. The analysis of different approaches to the interpretation and understanding of the concepts of «competence» and «awareness» makes it possible to conclude that it is necessary to distinguish these concepts. Thus, under the competence we understand a certain sphere, scope of activity, a predetermined system of questions, a personality should be well-informed about, that is, to have a set of knowledge, skills and own attitude towards them. Awareness is defined as the quality of the individual, his/her certain property, which is based on knowledge, experience, moral principles and manifests itself at a critical moment by the ability to find a connection between the situation and knowledge by making adequate solutions to the problem. Defining the priority of the competence approach in education is aimed at the transition to the new branch standards, that creates the preconditions for the implementation of key competences in the future professional activity of a future specialist according to the needs of the society and labor market requirements.
Keywords: компетенція; компетентність; компетентнісний підхід; кваліфікація; фахівець; competence; awareness; competence approach; qualification; specialist